(untitled) (Communication & Society, 2001)
Based on a content analysis of three national newspapers and three national television news programs this study tried to determine if the coverage of the Mexican 2000 presidential elections was fair and balanced, and the degree in which it focused on the discussion of the candidates proposals and programs. The findings show that while the coverage was mostly fair and balanced, the Mexican media reproduced the tendencies towards trivialization and spectacularization characteristic of the US press, presenting candidates as rivals engaged in an individual battle over personality, charisma, and verbal abilities to criticize and disqualify their adversaries.